The Relationship Between Self Confidence and Compliance Medication in Pulmonary Tuberculosis Patients - Zuliani (Al-Hijrah Indonesia, 2024)
Pulmonary tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis. Long treatment times cause sufferers to often be threatened with dropping out of treatment and feeling less productive because they suffer from pulmonary TB which will result in individuals having a low level of self-confidence within themselves. The aim of this research is to determine the relationship between self-confidence and adherence to taking medication in pulmonary TB sufferers at the Mojowarno Jombang Community Health Center. The method used in this research is Observational Analytical, with a Cross-Sectional approach. Amount 27 rospondents obtain using purposive sampling. The independent variable is self-confidence and the dependent variable is compliance with taking tuberculosis medication. The instruments used in this research were the TBSES-21 (Tuberculosis Self-Efficacy Scale) questionnaire and MMAS-8 (Morisky Medication Adherence Scale) compliance with chi square test data analysis. The results of this study showed that the majority of respondents had moderate confidence and were compliant in taking tuberculosis medication. After testing the research results, there was a relationship between belief and compliance with taking tuberculosis medication. Increase knowledge and foster motivation to carry out treatment as recommended by Health officials.